Austenitic stainless-steel plate, hydrogen gas piping, valves, fittings, and instruments

Austenitic stainless steel plates with controlled compositions and oxide films address hydrogen embrittlement issues, enhancing water-resistant gas fragility for hydrogen gas applications.

JP2025012086APending Publication Date: 2025-01-24NIPPON STEEL STAINLESS STEEL CORP
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
JP2023114652
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2023-07-12
Publication Date
2025-01-24

AI Technical Summary

Technical Problem

Existing austenitic stainless steel plates used for hydrogen gas piping are prone to hydrogen embrittlement when subjected to strain during processing, leading to reduced water-resistant gas fragility, as they have not been fully examined for this property.

Method used

Austenitic stainless steel plates with specific chemical compositions and oxide films are developed, featuring controlled element contents and thick oxide layers to enhance water-resistant gas fragility, with compositions optimized to stabilize the austenite phase and suppress hydrogen invasion.

Benefits of technology

The solution provides steel plates with enhanced resistance to hydrogen embrittlement, ensuring excellent water-resistant gas fragility even after strain, suitable for hydrogen gas piping, valves, and instruments.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025012086000001
    Figure 2025012086000001
  • Figure 2025012086000002
    Figure 2025012086000002
Patent Text Reader

Abstract

To provide an austenitic stainless-steel sheet excellent in hydrogen gas embrittlement resistance after imparting prestrain.SOLUTION: An austenitic stainless-steel plate has a base material and an oxide film, and the chemical composition of the base material comprises, in mass%, C: 0.100% or less, Si: 1.0% or less, Mn: 8.00 to 10.00%, P: 0.050% or less, S: 0.0050% or less, Cr: 14.0 to 18.0%, Mo: 1.0% or less, Ni: 6.0 to 9.0%, Cu: 1.50% or less, Co: 0.01 to 1.0%, N: 0.250% or less, Al: 0.10% or less, an optional element, and the balance Fe with inevitable impurities, wherein an M value [=551-462(C+N)-9.2Si-8.1Mn-13.7Cr-29(Ni+Cu)-18.2Mo] satisfies -90 or more to -20 or less, and the maximum value of an A value [=Cr+4Si+5Mo+10Al] from the top surface to a depth of 20 nm as measured by GDS is 30 or more, and wherein the plate has an oxide film thickness of 3 nm or more, a tensile strength of 550 MPa or more and a plate thickness of 4.5 mm or more.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to austenitic stainless steel plate, hydrogen gas piping, valves, fittings, and instruments. [Background technology]

[0002] In recent years, hydrogen gas has been attracting attention as a new energy source to replace fossil fuels. Hydrogen gas is a clean energy source that does not emit CO2. On the other hand, hydrogen gas can cause hydrogen embrittlement, which weakens materials. Therefore, Patent Document 1 discloses an austenitic stainless steel with improved resistance to hydrogen gas embrittlement. [Prior art documents] [Patent documents]

[0003] [Patent Document 1] JP 2015-196842 A Summary of the Invention [Problem to be solved by the invention]

[0004] In order to actually use hydrogen gas as an energy source, piping is required to transport the hydrogen gas. Austenitic stainless steel thick plate, which has excellent resistance to hydrogen gas embrittlement, is preferably used as the material for hydrogen gas piping.

[0005] When manufacturing pipes from thick steel plates, it is necessary to introduce a certain amount of strain into the steel plate as it is processed into a specified shape. However, when a certain amount of strain is introduced into a thick material and it is used in a hydrogen environment, there is a problem that hydrogen embrittlement is likely to occur.

[0006] In the austenitic stainless steel disclosed in Patent Document 1, sufficient consideration has not been given to the hydrogen gas embrittlement resistance after the above-mentioned pre-straining has been applied, and there is still room for improvement.

[0007] The present invention has an object to solve the above-mentioned problems and to provide an austenitic stainless steel sheet that has excellent resistance to hydrogen gas embrittlement after pre-straining, as well as hydrogen gas piping, valves, joints, and instruments using the same. [Means for solving the problem]

[0008] The present invention has been made to solve the above-mentioned problems, and the gist of the present invention is the following austenitic stainless steel plate, hydrogen gas piping, valves, joints, and instruments.

[0009] (1) A steel plate having a base material and an oxide film formed on a surface of the base material, The chemical composition of the base material is, in mass%, C: 0.100% or less, Si: 1.0% or less, Mn: 8.00-10.00%, P: 0.050% or less, S: 0.0050% or less, Cr: 14.0-18.0%, Mo: 1.0% or less Ni: 6.0-9.0%, Cu: 1.50% or less, Co: 0.01 to 1.0%, N: 0.250% or less, Al: 0.10% or less, Nb: 0-0.10%, Ti: 0 to 0.10%, B: 0~0.0050%, V: 0~0.50%, W: 0 to 0.50%, Ca: 0 to 0.0100%, Mg: 0 to 0.0100%, Zr: 0-0.50%, Ga: 0 to 0.050%, Hf: 0~0.10%, REM: 0~0.10%, The balance is Fe and impurities. The M value calculated by the following formula (i) is -90 or more and -20 or less, Using glow discharge optical emission spectroscopy, changes in the concentrations of O, Fe, Cr, Mn, Ni, Mo, Si, Al and N were measured in the depth direction from the outermost surface of the steel sheet, and the total amount of other elements excluding O was converted to 100% by mass. In the measurement results of the oxide film, the maximum value of A value calculated by the following formula (ii) is 30 or more, The thickness of the oxide film is 3 nm or more, The tensile strength is 550 MPa or more, The thickness of the steel plate is 4.5 mm or more. Austenitic stainless steel plate. M value=551-462(C+N)-9.2Si-8.1Mn-13.7Cr-29(Ni+Cu)-18.2Mo...(i) In the above formula (i), each element symbol represents the content (mass%) of each element contained in the base material, and when no element is contained, the element is represented as zero. A value = Cr + 4Si + 5Mo + 10Al (ii) In the above formula (ii), each element symbol represents the content (mass %) of each element measured at each depth position by glow discharge optical emission spectrometry, and when an element is not contained, it is set to zero.

[0010] (2) The chemical composition is, in mass%, Nb: 0.01 to 0.10%, Ti: 0.01 to 0.10%, B: 0.0002~0.0050%, V: 0.05~0.50%, W: 0.05 to 0.50%, Ca: 0.0002~0.0100%, Mg: 0.0002~0.0100%, Zr: 0.01 to 0.50%, Ga: 0.001 to 0.050%, Hf: 0.01 to 0.10%, and REM: 0.01~0.10%, Contains one or more selected from The austenitic stainless steel sheet according to (1) above.

[0011] (3) The austenitic stainless steel sheet according to (1) or (2) above is used. Hydrogen gas piping.

[0012] (4) connected to the hydrogen gas piping described in (3) above, The austenitic stainless steel sheet according to (1) or (2) above is used. Valves, fittings, or instruments. Effect of the Invention

[0013] According to the present invention, it is possible to obtain an austenitic stainless steel sheet having excellent resistance to hydrogen gas embrittlement after pre-straining, as well as hydrogen gas piping, valves, joints, and instruments using the same. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0014] The present inventors have investigated methods for improving hydrogen gas embrittlement resistance after pre-straining, and have obtained the following findings.

[0015] (a) Steel plates used in piping for transporting hydrogen gas are exposed to hydrogen gas at pressures of about 0.1 to 20 MPa at temperatures from room temperature to less than about 500°C. In this case, hydrogen permeates from the environment into the steel, causing so-called hydrogen embrittlement, making the steel more susceptible to fracture.

[0016] (b) In addition, when manufacturing pipes from thick steel plates, plastic deformation such as tension and bending is performed. Such plastic deformation imparts pre-strain to the thick steel plates, making them more susceptible to hydrogen embrittlement.

[0017] (c) As a result of the inventors' investigation into methods for suppressing hydrogen penetration into steel, they found that forming an oxide film mainly composed of Cr2O3 on the surface of the steel sheet is effective in suppressing hydrogen penetration. Furthermore, the solid solution of Si, Mo, and Al in the oxide film is also effective. It is believed that these elements improve the density of the oxide film and suppress hydrogen penetration.

[0018] (d) In addition, by performing a preliminary oxidation treatment and making the oxide film sufficiently thick, it is possible to suppress the penetration of hydrogen even in a state in which pre-strain is applied.

[0019] An embodiment of the present invention has been made based on the above findings. Each requirement of this embodiment will be described in detail below.

[0020] 1. Overall structure The austenitic stainless steel sheet according to this embodiment has a base material and an oxide film formed on the surface of the base material.

[0021] 2. Chemical composition of the base material The reasons for limiting the content of each element are as follows. In the following description, "%" for the content means "mass %."

[0022] C: 0.100% or less C is an element effective in stabilizing the austenite phase, and also contributes to improving hydrogen gas embrittlement resistance. However, excessive C content promotes grain boundary precipitation of Cr-based carbides, which easily form the starting point of fracture. As a result, hydrogen gas embrittlement resistance is actually reduced. For this reason, the C content is set to 0.100% or less. The C content is preferably set to 0.080% or less, and more preferably set to 0.060% or less. On the other hand, in order to obtain the above effect, the C content is preferably set to 0.010% or more.

[0023] Si: 1.0% or less Silicon is an effective element for deoxidization and also contributes to improving hydrogen gas embrittlement resistance. However, excessive silicon content promotes the formation of intermetallic compounds such as σ phase, which reduces hot workability and toughness. For this reason, the silicon content is set to 1.0% or less. The silicon content is preferably set to 0.70% or less, and more preferably set to 0.50% or less. On the other hand, in order to obtain the above effects, the silicon content is preferably set to 0.30% or more.

[0024] Mn: 8.00-10.00% Mn is an element effective in stabilizing the austenite phase, and contributes to improving hydrogen gas embrittlement resistance. It also has the effect of improving strength. For this reason, the Mn content is set to 8.00% or more. The Mn content is preferably set to 8.50% or more. However, excessive Mn content promotes the formation of ε phase, which is highly susceptible to hydrogen embrittlement, and instead reduces hydrogen gas embrittlement resistance. For this reason, the Mn content is set to 10.00% or less. The Mn content is preferably set to 9.50% or less, and more preferably set to 9.00% or less.

[0025] P:0.050% or less P is an element contained in steel as an impurity, which causes segregation and reduces hydrogen gas embrittlement resistance. Therefore, the P content is set to 0.050% or less. The P content is preferably set to 0.040% or less, and more preferably set to 0.030% or less. On the other hand, excessive reduction of P leads to an increase in manufacturing costs, so the P content is preferably set to 0.010% or more.

[0026] S: 0.0050% or less S is an element contained in steel as an impurity, and forms MnS, which reduces hydrogen gas embrittlement resistance. Therefore, the S content is set to 0.0050% or less. The S content is preferably set to 0.0040% or less, and more preferably set to 0.0030% or less. However, excessive reduction of the S content increases the manufacturing cost. Therefore, the S content is preferably set to 0.0002% or more.

[0027] Cr: 14.0~18.0% Cr is an element contained in a certain amount in stainless steel, and has the effect of improving corrosion resistance. Therefore, the Cr content is set to 14.0% or more. The Cr content is preferably set to 14.5% or more, and more preferably set to 15.0% or more. However, Cr is a ferrite forming element. Therefore, if Cr is contained in excess, the austenite phase is destabilized and the hydrogen gas embrittlement resistance is reduced. Therefore, the Cr content is set to 18.0% or less. The Cr content is preferably set to 17.5% or less, and more preferably set to 16.5% or less.

[0028] Mo: 1.0% or less Mo has the effect of improving strength. However, if it is contained in excess, it promotes the formation of δ-ferrite phase and reduces hydrogen gas embrittlement resistance. For this reason, the Mo content is set to 1.0% or less. The Mo content is preferably set to 0.70% or less, and more preferably set to 0.50% or less. On the other hand, if the Mo content is excessively reduced, it will lead to restrictions on the melting raw materials and increase the manufacturing cost. For this reason, the Mo content is preferably set to 0.01% or more, and more preferably set to 0.05% or more.

[0029] Ni: 6.0~9.0% Ni, together with Mn, is an element necessary for ensuring hydrogen gas embrittlement resistance. Therefore, the Ni content is set to 6.0% or more. The Ni content is preferably set to 6.5% or more, and more preferably set to 7.0% or more. However, excessive Ni content increases the manufacturing cost. Also, segregation is likely to occur. Therefore, the Ni content is set to 9.0% or less. The Ni content is preferably set to 8.5% or less, and more preferably set to 7.6% or less.

[0030] Cu:1.50% or less Cu is an element that is mixed in from raw materials such as scrap, and is an element that is effective in stabilizing the austenite phase. On the other hand, Cu is a low melting point element that segregates at grain boundaries and easily generates fracture starting points. For this reason, the Cu content is set to 1.50% or less. The Cu content is preferably set to 1.00% or less, and more preferably set to 0.50% or less. However, excessive reduction of the Cu content leads to restrictions on the melting raw materials and increases the manufacturing cost. For this reason, the Cu content is preferably set to 0.01% or more, and more preferably set to 0.05% or more.

[0031] Co: 0.01 to 1.0% Co has the effect of improving corrosion resistance and stabilizing the austenite phase. In particular, when the plate thickness is large, it has the effect of improving hydrogen gas embrittlement resistance. For this reason, the Co content is set to 0.01% or more. The Co content is preferably 0.05% or more, and more preferably 0.10% or more. However, if Co is contained in excess, toughness and workability decrease. For this reason, the Co content is set to 1.0% or less. The Co content is preferably 0.70% or less.

[0032] N: 0.250% or less Like Mn and Ni, N is an element effective in improving hydrogen gas embrittlement resistance. However, if N is contained in excess, internal defects such as blowholes during melting may occur, which may lead to a decrease in hydrogen gas embrittlement resistance. For this reason, the N content is set to 0.250% or less. The N content is preferably set to 0.200% or less, and more preferably set to 0.100% or less. On the other hand, in order to obtain the above effect, the N content is preferably set to 0.010% or more.

[0033] Al: 0.10% or less Al is an effective deoxidizing element, and also has the effect of suppressing the grain boundary segregation of low melting point elements and strengthening the grain boundaries. However, Al is a ferrite forming element. Therefore, if Al is contained in excess, the austenite phase becomes unstable. For this reason, the Al content is set to 0.10% or less. The Al content is preferably 0.05% or less. On the other hand, in order to obtain the above effect, the Al content is preferably 0.01% or more.

[0034] In addition to the above elements, one or more elements selected from Nb, Ti, B, V, W, Ca, Mg, Zr, Ga, Hf, and REM may be contained within the ranges shown below. The reasons for limiting each element will be explained.

[0035] Nb: 0 to 0.10% Nb has the effect of forming carbonitrides, refining crystal grains, and strengthening grain boundaries. Therefore, it may be contained as necessary. However, if Nb is contained in excess, the manufacturability and workability during hot rolling decrease. For this reason, the Nb content is set to 0.10% or less. The Nb content is preferably set to 0.07% or less. On the other hand, in order to obtain the above effect, the Nb content is preferably set to 0.01% or more.

[0036] Ti: 0 to 0.10% Ti has the effect of forming carbonitrides, refining crystal grains, and strengthening grain boundaries. Therefore, it may be contained as necessary. However, if Ti is contained in excess, the manufacturability during hot rolling decreases. Therefore, the Ti content is set to 0.10% or less. The Ti content is preferably set to 0.070% or less, more preferably set to 0.050% or less, and even more preferably set to 0.020% or less. On the other hand, in order to obtain the above effect, the Ti content is preferably set to 0.001% or more.

[0037] B: 0 to 0.0050% B has the effect of strengthening grain boundaries and improving strength. Therefore, it may be contained as necessary. However, even if an excessive amount of B is contained, the effect is saturated. Therefore, the B content is set to 0.0050% or less. The B content is preferably set to 0.0030% or less. On the other hand, in order to obtain the above effect, the B content is preferably set to 0.0002% or more.

[0038] V: 0~0.50% V has the effect of improving strength by dissolving in steel or precipitating as carbonitrides. Therefore, V may be contained as necessary. However, if an excessive amount of V is contained, excessive carbonitrides are formed, which reduces manufacturability during hot rolling. Therefore, the V content is preferably 0.50% or less. The V content is preferably 0.30% or less. On the other hand, in order to obtain the above effect, the V content is preferably 0.05% or more.

[0039] W: 0~0.50% W has the effect of improving strength and corrosion resistance. Therefore, it may be contained as necessary. However, excessive W content increases the manufacturing cost. Therefore, the W content is set to 0.50% or less. The W content is preferably set to 0.30% or less. On the other hand, in order to obtain the above effect, the W content is preferably set to 0.05% or more.

[0040] Ca: 0 to 0.0100% Ca has the effect of suppressing the grain boundary segregation of low melting point elements and strengthening the grain boundary. Therefore, it may be contained as necessary. However, if Ca is contained in excess, segregation is likely to occur and it is likely to become the starting point of fracture. For this reason, the Ca content is set to 0.0100% or less. The Ca content is preferably set to 0.0050% or less. On the other hand, in order to obtain the above effect, the Ca content is preferably set to 0.0002% or more.

[0041] Magnesium: 0 to 0.0100% Mg has the effect of suppressing the grain boundary segregation of low melting point elements and strengthening the grain boundary. Therefore, it may be contained as necessary. However, if Mg is contained in excess, a large amount of inclusions are formed, which tend to become the starting point of fracture. For this reason, the Mg content is set to 0.0100% or less. The Mg content is preferably set to 0.0050% or less. On the other hand, in order to obtain the above effect, the Mg content is preferably set to 0.0002% or more.

[0042] Zr: 0 to 0.50% Zr has a deoxidizing effect. It also has the effect of improving corrosion resistance. Therefore, it may be contained as necessary. However, if Zr is contained in excess, toughness and workability decrease. Also, a large amount of inclusions are formed, which tend to become the starting point of fracture. For this reason, the Zr content is set to 0.50% or less. The Zr content is preferably set to 0.30% or less. On the other hand, in order to obtain the above effects, the Zr content is preferably set to 0.01% or more.

[0043] Ga: 0 to 0.050% Ga has the effect of improving hot workability. Therefore, it may be contained as necessary. However, excessive Ga content reduces manufacturability. Therefore, the Ga content is set to 0.050% or less. The Ga content is preferably set to 0.030% or less. On the other hand, in order to obtain the above effect, the Ga content is preferably set to 0.001% or more.

[0044] Hf: 0~0.10% Hf has the effect of improving strength and hydrogen gas embrittlement resistance. Therefore, it may be contained as necessary. However, if an excessive amount of Hf is contained, workability decreases. Therefore, the Hf content is set to 0.10% or less. The Hf content is preferably set to 0.07% or less. On the other hand, in order to obtain the above effect, the Hf content is preferably set to 0.01% or more.

[0045] REM: 0~0.10% REM has the effect of improving hot workability. It also has the effect of improving corrosion resistance. Therefore, it may be contained as necessary. However, if REM is contained in excess, not only will the effect saturate, but the hot workability will also decrease. For this reason, the REM content is set to 0.10% or less. The REM content is preferably set to 0.07% or less. On the other hand, in order to obtain the above effects, the REM content is preferably set to 0.01% or more.

[0046] REM refers to a total of 17 elements, including Sc, Y and lanthanides, and the above REM content refers to the total content of these elements. In industry, REM is often added in the form of misch metal.

[0047] In the chemical composition of this embodiment, the balance is Fe and impurities. Here, "impurities" refer to components that are mixed in due to various factors in raw materials such as ores and scraps and in the manufacturing process during industrial production of austenitic stainless steel sheets, and are permissible within a range that does not adversely affect this embodiment.

[0048] M Value The M value calculated by the following formula (i) is an index showing the stability of the γ phase in an austenitic stainless steel sheet. In the austenitic stainless steel sheet of the present embodiment, the M value is set to be −90 or more and −20 or less in order to improve resistance to hydrogen gas embrittlement. M value=551-462(C+N)-9.2Si-8.1Mn-13.7Cr-29(Ni+Cu)-18.2Mo...(i) In the above formula (i), each element symbol represents the content (mass%) of each element contained in the base material, and if the element is not contained, it is set to zero.

[0049] By setting the M value to -20 or less, it is possible to ensure the stability of the γ phase, suppress the transformation to the α′ phase, and improve the resistance to hydrogen gas embrittlement. The M value is more preferably set to -30 or less, and further preferably set to -40 or less.

[0050] On the other hand, in order to make the M value less than -90, a large amount of additive elements is required, which increases the alloy cost. Therefore, the M value is set to -90 or more. The M value is more preferably set to -80 or more, and further preferably set to -70 or more.

[0051] 2. Oxide film As mentioned above, in order to suppress the penetration of hydrogen into steel, it is important to form an oxide film that is mainly composed of Cr2O3 and contains solid solutions of Si, Mo, and Al to a certain thickness or more. In other words, in order to improve the hydrogen gas embrittlement resistance after pre-straining, it is important to control the chemical composition and thickness of the oxide film.

[0052] In the present invention, the chemical composition and thickness of the oxide film are measured by glow discharge optical emission spectroscopy (GDS). Specifically, GDS is used to measure the concentration changes of O, Fe, Cr, Mn, Ni, Mo, Si, Al, and N in the depth direction from the outermost surface of the steel sheet, and the total amount of other elements excluding O is converted to 100% by mass.

[0053] From the above viewpoint, in this embodiment, in the measurement results of the oxide film, the maximum value of A calculated by formula (i) is set to 30 or more, and the thickness of the oxide film is set to 3 nm or more.

[0054] A value The A value is an index of the ability of an oxide film to suppress hydrogen penetration. In the austenitic stainless steel sheet of this embodiment, in order to improve resistance to hydrogen gas embrittlement, the maximum A value calculated at each depth position in the region from the outermost surface of the steel sheet to a depth position of 20 nm is set to be 30 or more. A value = Cr + 4Si + 5Mo + 10Al (ii) In the above formula (ii), each element symbol represents the content (mass %) of each element measured at each depth position by glow discharge optical emission spectrometry, and when an element is not contained, it is set to zero.

[0055] The oxide film is usually composed mainly of oxides of Fe and Cr depending on the chemical composition of the base material. As a result of the study by the inventors, it was found that it is possible to increase the ratio of Cr oxide and dissolve Si, Mo, and Al in the oxide film by optimizing the manufacturing conditions.

[0056] If the maximum value of A is less than 30, the ratio of Fe oxide is excessive, and the effect of suppressing hydrogen penetration into the steel is not sufficiently obtained. The maximum value of A is preferably 35 or more, more preferably 40 or more, and even more preferably 45 or more. Since a higher maximum value of A is preferable, there is no need to set an upper limit, but 80 is the upper limit that can be practically produced.

[0057] Oxide film thickness As described above, even in a state where prestrain is applied, the oxide film needs to be sufficiently thick in order to suppress the penetration of hydrogen. From this viewpoint, in this embodiment, the oxide film is set to have a thickness of 3 nm or more. The thickness of the oxide film is preferably 5 nm or more, more preferably 10 nm or more, and further preferably 20 nm or more.

[0058] The GDS analysis is performed at any one point selected from an area with few surface defects. At the measurement point, the steel sheet is sputtered from the outermost surface to a depth of 50 nm, while measuring the elemental concentrations of O, Fe, Cr, Mn, Ni, Mo, Si, Al, and N at a pitch of 0.8 to 1.2 nm. This determines the content (mass%) of the above elements at each depth. At this time, the total amount of other elements excluding O is converted to 100% by mass. The GDS analysis is also performed at a depth of 1000 nm from the outermost surface of the steel sheet, and the content of each element is determined in the same manner.

[0059] Next, the obtained Cr concentration profile is referenced to identify the depth position where the Cr content is maximum. Then, the average value of the maximum Cr content and the Cr content at a depth position 1000 nm from the outermost surface is calculated. Next, the Cr content is confirmed in the depth direction (toward the base material) from the depth position where the Cr content is maximum, and the depth position where the Cr content first falls below the above average value is defined as the boundary between the base material and the oxide film. Based on the result, the thickness of the oxide film is calculated. In addition, the above A value is calculated at each depth position in the region identified as the oxide film, and the maximum A value is calculated from all the calculated measured values.

[0060] As a GDS measuring device, for example, a GD-Profiler2 device manufactured by Horiba, Ltd. can be used, and the measurement conditions can be 35 W, argon pressure 600 Pa, frequency 100 Hz, and measurement diameter 4 mmφ.

[0061] 3. Mechanical properties The austenitic stainless steel plate of this embodiment has a tensile strength of 550 MPa or more. This makes it possible to ensure sufficient strength when used as hydrogen gas piping or the like. The tensile strength is preferably 570 MPa or more. The tensile strength is measured in accordance with JIS Z 2241:2022. For the measurement, a JIS 14B test piece or a 14A test piece, as specified in JIS Z 2241:2022, is used, which is taken from the center position of the plate thickness so that the longitudinal direction is perpendicular to the rolling direction of the steel plate. More specifically, when the plate thickness is 5 mm or less, the thickness of the test piece is the original thickness, and when the plate thickness is more than 5 mm and less than 12 mm, the thickness is reduced to 5 mm to make a 14B test piece. On the other hand, when the plate thickness is 12 mm or more, a round bar 14A test piece is used.

[0062] 4. Plate thickness The plate thickness of the austenitic stainless steel plate in this embodiment is 4.5 mm or more. This is because the strength required for a liquefied hydrogen storage tank can be ensured by setting the plate thickness within the above range. The plate thickness is preferably 10 mm or more, and more preferably 20 mm or more. When used for a larger liquefied hydrogen storage tank, the plate thickness is preferably 30 mm or more. The upper limit of the plate thickness is not particularly limited, but is usually 100 mm.

[0063] 5.Applications The austenitic stainless steel sheet of this embodiment has excellent resistance to hydrogen gas embrittlement after prestraining, and is therefore preferably used as a material for hydrogen gas piping. The austenitic stainless steel sheet of this embodiment can also be suitably used as a material for valves, joints, or meters connected to hydrogen gas piping. The hydrogen gas may be either compressed gas or gas obtained by vaporizing liquefied hydrogen, and the pressure of the hydrogen gas is, for example, within the range of 0.1 to 20 MPa, and the temperature is, for example, from room temperature to less than 500°C.

[0064] 6. Manufacturing method A preferred method for producing the austenitic stainless steel sheet of this embodiment will now be described. The austenitic stainless steel sheet of this embodiment can be stably produced, for example, by the following production method.

[0065] Stainless steel having the above chemical composition is melted and a steel billet such as a slab is manufactured. Next, the steel billet is heated to a predetermined temperature and hot rolled (hot rolling process). The heating temperature in hot rolling is preferably in the range of 1050 to 1250°C, and the rolling reduction is preferably 40% or more. By setting the heating temperature and rolling reduction in the above ranges during hot rolling, it becomes easier to control the plate thickness to the desired thickness.

[0066] Following the hot rolling step, a descaling step and a preliminary oxidation step are performed. In the descaling step, scale formed during hot rolling is removed by pickling or polishing. When pickling is performed, for example, the steel sheet is immersed in a nitric hydrofluoric acid aqueous solution at 40 to 80°C for 1 to 30 minutes. When polishing is performed, polishing is performed until the metal surface can be confirmed.

[0067] In the pre-oxidation step following the descaling step, heating is performed for 1 to 24 hours in an atmosphere of air or LNG, or in a mixed atmosphere of two or more selected from air, LNG, and hydrogen, at a temperature range of 100°C to 500°C. By performing the pre-oxidation step following the descaling step, the maximum A value can be made 30 or more, and the thickness of the oxide film can be made 3 nm or more.

[0068] EXAMPLES The austenitic stainless steel sheet according to the present invention will be described more specifically below with reference to examples, but the present embodiment is not limited to these examples. EXAMPLES

[0069] Stainless steel having the chemical composition shown in Table 1 was melted and a slab was manufactured. The slab was then heated in the range of 1050 to 1250°C and hot rolled. After hot rolling, a descaling process and a preliminary oxidation process were performed under the conditions shown in Table 2 to obtain an austenitic stainless steel sheet. Note that "LNG" in the table refers to an LNG combustion simulated atmosphere, which was 1% O2-72% N2-10% CO2-17% H2O.

[0070] [Table 1]

[0071] [Table 2]

[0072] Measurement of chemical composition and thickness of oxide film For each of the obtained austenitic stainless steel sheets, analysis by GDS was performed at any one point selected from the range with few surface defects. At the measurement point, the steel sheet was sputtered from the outermost surface to a depth of 50 nm, while measuring the elemental concentrations of O, Fe, Cr, Mn, Ni, Mo, Si, Al and N at a pitch of about 1 nm, and the contents (mass%) of the above elements at each depth were determined. At this time, the total amount of other elements excluding O was converted to 100% by mass. Analysis by GDS was also performed at a depth of 1000 nm from the outermost surface of the steel sheet, and the contents of each element were similarly determined.

[0073] Next, the depth position where the Cr content is maximum was identified by referring to the obtained Cr concentration profile, and the average value of the maximum Cr content and the Cr content at a depth position 1000 nm from the outermost surface was calculated. Next, the Cr content was confirmed in the depth direction (base material side) from the depth position where the Cr content was maximum, and the depth position where the Cr content first fell below the above average value was determined as the boundary between the base material and the oxide film. Based on the result, the thickness of the oxide film was calculated. In addition, the above A value was calculated at each depth position in the region identified as the oxide film, and the maximum A value was calculated from all the calculated measured values.

[0074] The GDS measurement device used was a GD-Profiler2 manufactured by Horiba, Ltd., and the measurement conditions were 35 W, argon pressure 600 Pa, frequency 100 Hz, and measurement diameter 4 mmφ.

[0075] Strength evaluation test A tensile test was conducted to evaluate the strength. The tensile strength (TS) was measured in accordance with JIS Z 2241:2022. For the measurement, a round bar No. 14A test piece, as specified in JIS Z 2241:2022, was used, which was taken from the center of the plate thickness so that the longitudinal direction was perpendicular to the rolling direction of the steel plate.

[0076] Hydrogen gas embrittlement resistance evaluation test Tensile tests were conducted to evaluate hydrogen gas embrittlement resistance. Tensile test pieces with a parallel cross-sectional thickness of 15 mm, width of 20 mm, and length of 80 mm were taken from the 1 / 2 position of the steel plate, with the longitudinal direction perpendicular to the rolling direction. When the plate thickness was less than 15 mm, tensile test pieces with a parallel cross-sectional thickness of the original plate thickness, width of 20 mm, and length of 80 mm were taken. This test piece was pulled in air at a tensile speed of 1.2 mm / min until the displacement of the parallel part reached 16 mm, and a pre-strain of 20% was applied.

[0077] A round bar tensile test specimen with a parallel diameter of 6 mm and an original rating distance of 30 mm was prepared from the parallel part of the pre-strained test specimen. This tensile test specimen was heated again under the pre-oxidation conditions shown in Table 2. The heated tensile test specimen was then placed in a pressure vessel, the inside of the vessel was replaced with hydrogen gas, and the specimen was then heated and pressurized to be held in an environment of 10 MPa and 300°C for 100 hours.

[0078] The test pieces were then taken out of the pressure vessel and immediately placed in a room temperature / air environment, where tensile stress was applied until breakage. The tensile speed was 0.09mm / min up to 0.2% yield strength, and 1.2mm / min thereafter. In order to calculate the RTS (relative tensile strength) and REL (relative elongation at break) for each test piece, which will be described later, the tensile strength and elongation at break were also measured separately for the heated tensile test pieces.

[0079] The test results were evaluated in terms of RTS (relative tensile strength) and REL (relative elongation at break). RTS and REL are calculated using the following formulas. RTS = Tensile strength at room temperature in air after prestrain in air + heat treatment + hydrogen charging ÷ Tensile strength at room temperature in air after prestrain in air + heat treatment REL = Tensile strength at room temperature in air after prestrain in air + heat treatment + hydrogen charging ÷ Breaking elongation at room temperature in air after prestrain in air + heat treatment

[0080] When the RTS was 0.95 or more, the hydrogen gas embrittlement resistance was judged to be good and marked with ◯. When the RTS was 0.95 or more and the REL was 0.95 or more, the hydrogen gas embrittlement resistance was judged to be even better and marked with ⊚. The results are also shown in Table 2. [Industrial Applicability]

[0081] The austenitic stainless steel sheet of this embodiment has excellent resistance to hydrogen gas embrittlement after pre-straining, and is therefore suitable as a material for hydrogen gas piping, as well as valves, joints, and instruments connected thereto.

Claims

1. A steel plate having a base material and an oxide film formed on a surface of the base material, The chemical composition of the base material is, in mass%, C: 0.100% or less, Si: 1.0% or less, Mn: 8.00-10.00%, P: 0.050% or less, S: 0.0050% or less, Cr: 14.0-18.0%, Mo: 1.0% or less, Ni: 6.0 to 9.0%, Cu: 1.50% or less, Co: 0.01 to 1.0%, N: 0.250% or less, Al: 0.10% or less, Nb: 0 to 0.10%, Ti: 0 to 0.10%, B: 0 to 0.0050%, V: 0-0.50%, W: 0-0.50%, Ca: 0-0.0100%, Mg: 0 to 0.0100%, Zr: 0 to 0.50%, Ga: 0 to 0.050%, Hf: 0-0.10%, REM: 0-0.10%, The balance is Fe and impurities. The M value calculated by the following formula (i) is -90 or more and -20 or less, Using glow discharge optical emission spectroscopy, changes in the concentrations of O, Fe, Cr, Mn, Ni, Mo, Si, Al and N were measured in the depth direction from the outermost surface of the steel sheet, and the total amount of other elements excluding O was converted to 100% by mass. In the measurement results of the oxide film, the maximum value of A value calculated by the following formula (ii) is 30 or more, The thickness of the oxide film is 3 nm or more, The tensile strength is 550 MPa or more, The thickness of the steel plate is 4.5 mm or more. Austenitic stainless steel plate. M value=551-462(C+N)-9.2Si-8.1Mn-13.7Cr-29(Ni+Cu)-18.2Mo...(i) In the above formula (i), each element symbol represents the content (mass%) of each element contained in the base material, and when the element is not contained, it is set to zero. A value = Cr + 4Si + 5Mo + 10Al ... (ii) In the above formula (ii), each element symbol represents the content (mass%) of each element measured at each depth position by glow discharge optical emission spectrometry, and if the element is not contained, it is set to zero.

2. The chemical composition, in mass%, Nb: 0.01 to 0.10%, Ti: 0.01 to 0.10%, B: 0.0002 to 0.0050%, V: 0.05-0.50%, W: 0.05-0.50%, Ca: 0.0002-0.0100%, Mg: 0.0002 to 0.0100%, Zr: 0.01 to 0.50%, Ga: 0.001-0.050%, Hf: 0.01 to 0.10%, and REM: 0.01-0.10%, Contains one or more selected from The austenitic stainless steel sheet according to claim 1.

3. The austenitic stainless steel sheet according to claim 1 or 2 is used. Hydrogen gas piping.

4. A hydrogen gas pipe according to claim 3 is connected to the hydrogen gas pipe, The austenitic stainless steel sheet according to claim 1 or 2 is used. Valves, fittings, or instruments.

Citation Information

Patent Citations

  • Austenitic stainless steel excellent in hot workability and hydrogen embrittlement resistance and production method therefor

    JP2015196842A